ANALISIS PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN PEMIDANAAN PERKARA TINDAK PIDANA KEFARMASIAN DALAM PUTUSAN NOMOR: 29/PID.SUS/2024/PN SLT - Istizanah Nurlatifah; Dara Pustika Sukma (Sebelas Maret University, 2026)
This study aims to analyze whether the judge's considerations in rendering a criminal sentencing decision in the pharmaceutical crime case, Verdict Number: 29/Pid.Sus/2024/PN Slt, comply with the provisions of Article 183 of the Indonesian Criminal Procedure Code (KUHAP). This study was normative legal research with a prescriptive and applied nature. The approach used in this study was a case study. Primary and secondary legal materials were collected through library research and analyzed using deductive syllogism techniques. Based on the results of research and discussion, it is concluded that the judge's considerations in ruling on the pharmaceutical criminal case in Verdict Number 29/Pid.Sus/2024/PN Slt are in accordance with Article 183 of the Indonesian Criminal Procedure Code (KUHAP), as there are four (4) valid pieces of evidence in the case that convinced the judge that the defendant was indeed guilty of distributing pharmaceutical products that did not meet the required standards and must be held accountable for his action.